Atmospheric conditions affecting the transmission of COVID-19 virus - Shoor, Purva; Kaur, Gagan Deep; Chauhan, Amanjot Kaur (International Journal Of Community Medicine And Public Health, 2021)
The physical environment plays an important role in the transmission of respiratory infections like COVID-19. Atmospheric conditions associated to diseases like influenza, adenovirus infections, parainfluenza, common cold viruses and so on. But we are still lacking in evidence to support the influence of meteorological conditions in spreading COVID-19. We have discussed air pollution, smoking, low air temperature, and proximity to equator, low humidity and air velocity as contributing factors in the spread of SARS-CoV-2 through this narrative synthesis. Bio-aerosol or ultra-fine particulate matter seems to be the most promising mode of transmission of COVID-19. Other methods are direct contact and droplet infection. Air pollution control can prevent priming of respiratory system which shall further protect from pulmonary infections. Air sanitization and humidifiers can be considered to modify the indoor air and prevent contracting infection at workplaces, schools and other gatherings.